A Remote Sensing Approach in Detecting Landslide Susceptibility in Ngadas Village - Saputra, Aswin Nur; Riyanto, Agus; Azzahra, Nabiela; Putri, Amalia; Azizah, Khifayatul; Awaliah, Siti (Universitas Lambung Mangkurat, 2025)
This study explores the use of remote sensing techniques to assess landslide severity in Ngadas Village, a mountainous area prone to landslides due to its steep topography. Located in Poncokusumo District, Malang Regency, Ngadas Village serves a strategic role as a gateway to Bromo Tengger Semeru National Park (TNBTS). Its significance in tourism and agriculture underscores the importance of mitigating landslide risks that could disrupt accessibility and local livelihoods. By integrating remote sensing data such as Digital Elevation Models (DEM), satellite imagery, rainfall patterns, soil types, and geological characteristics, this study employs weighted overlay analysis to produce a comprehensive landslide vulnerability map. The findings reveal that landslide vulnerability in the Ngadas region varies but is predominantly moderate to low. This is largely due to the rainfall parameter, which holds the highest weight (30%), making it the dominant influencing factor. In years of high rainfall, landslide vulnerability in Ngadas is expected to increase significantly. Conversely, soil type contributes minimally to the vulnerability assessment, as the region’s soil has inherently loose properties. This spatial analysis provides valuable insights for disaster mitigation planning, highlighting the need for adaptive land management strategies to enhance resilience and sustainability in the area.